POLITICAL ACTIVIST COMMUNITY PORTRAIT IN LEILA S. CHUDORI’S NOVEL LAUT BERCERITA - Efendi Barus; Saiful Anwar Matondang; M. Manugeren; Purwarno Purwarno; Purwanto Siwi; Susi Ekalestari; Sri Wulan (University of Kuningan, 2023)
In the process of democratization in a state, the position of university students is decisive. Every student must be responsible to the society, able to see what is happening and to provide the best solutions to the societal problems as well as being a mouthpiece from the common people to the government, nation and state. In addition to developing their cognitive abilitie0s, students are required to participate actively in everything that is social in nature to foster a social spirit in the community. This picture is reflected in the political activist community in the novel Laut Bercerita by Leila S. Chudori. The research was conducted using a literary sociology approach related to the author's relationship with society and texts revealing problems in society. The focus of the research is related to the disclosure of social phenomena. Holistically, a qualitative descriptive research method is implemented. The data source is the novel and data collection is based on documentation techniques, obtained from the novel in the forms text referring to the attitudes of the students in their struggle for reform in all areas of public life and also based on the content analysis techniques with an objective approach. The results of the study show that the attitudes reflected in the political activist movement are social awareness, hard work and tolerance.